EFEKTIVITAS PENERAPAN MEDIA PEMBELAJARAN INKUIRI TERBIMBING TERHADAP KEMAMPUAN BERFIKIR KRITIS DAN HASIL BELAJAR SISWA PADA MATA PELAJARAN BAHASA INDONESIA KELAS V SD NEGERI 07 LIMO KOTO - Dira Oktavia; Fetri Yeni J; Mutiara Felicita Amsal; Elsa Masriani (STKIP Subang, 2026)
This research was motivated by the low critical thinking skills and learning outcomes of students in Indonesian language subjects in grade V at SD Negeri 07 Limo Koto. This was due to the learning process which was still dominated by the lecture method, causing students to be less active. This study aims to analyze the effectiveness of the Guided Inquiry learning model on students' critical thinking skills and learning outcomes. The research method used was quantitative with a one-group pretest-posttest design. The research subjects consisted of 19 fifth-grade students. The research instrument was a validated critical thinking skills test. Data were analyzed using the paired sample t-test through SPSS. The results showed a significant increase in the average score from 56.63 during the pretest to 80.42 during the posttest. The hypothesis test results showed a significance value of 0.000 < 0.05, which means it can be concluded that the implementation of the Guided Inquiry learning model is effective in improving students' critical thinking skills and learning outcomes in Indonesian language subjects.